2011
DOI: 10.1111/j.1751-7133.2011.00260.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Carbohydrate Antigen 125 Levels in Nonischemic Dilated Cardiomyopathy: A Useful Biomarker for Prognosis and Functional Mitral Regurgitation

Abstract: The authors investigated the prognostic relevance of serum carbohydrate antigen 125 (CA125) levels in nonischemic dilated cardiomyopathy (NICMP) and assessed whether increased levels relate to the degree of functional mitral regurgitation (FMR). Seventy-seven patients with NICMP were enrolled and followed-up for 10 ± 2 months in this prospective study. Receiver-operating characteristic analysis established a cutoff CA125 value of 25 U/mL for predicting mortality. Patients were divided into two groups according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
(51 reference statements)
1
7
0
Order By: Relevance
“…MUC16 is also known as CA125, whose protein product is the tumor marker carbohydrate antigen 125. Serum carbohydrate antigen 125 level is reportedly correlated with DCM prognosis and clinical severity [17,18] . FBN1 was mostly reported as a causal gene of Marfan syndrome [19,20] while in this study, we found the association of FBN1 and DCM, which will be reported in another work of our team.…”
Section: Discussionmentioning
confidence: 99%
“…MUC16 is also known as CA125, whose protein product is the tumor marker carbohydrate antigen 125. Serum carbohydrate antigen 125 level is reportedly correlated with DCM prognosis and clinical severity [17,18] . FBN1 was mostly reported as a causal gene of Marfan syndrome [19,20] while in this study, we found the association of FBN1 and DCM, which will be reported in another work of our team.…”
Section: Discussionmentioning
confidence: 99%
“…By careful examination of all clinical features with transient CA-125 elevation, we found that pro-BNP levels after surgery were strongly correlated with transient elevation of serum CA-125 in NSCLC patients (Figure 1B) p=0.00035 (Table 2). Several previous studies have shown that both CA-125 and pro-BNP was significantly related with heart function in heart disease patients, and the CA-125 levels were positively correlated with pro-BNP in heart disease patients [21][22][23] . Pro-BNP is a quantitative biomarker of myocardial function.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that CA-125 level is significantly associated with LV cardiac failure in hemodialysis patients. Several studies have implicated the role of CA-125 level in congestive heart failure (CHF) (17) as well as nonischemic dilated cardiomyopathy (18). In a study on 77 male patients with CHF, it was shown that CA-125 levels were associated with CHF severity (determined by NYHA classification) and fluid overload defined by pulmonary congestion and ankle edema (19).…”
Section: Discussionmentioning
confidence: 99%